Personal Liability For Loss Of Business Of Consumer In Electronic Transaction Using The Standard Contract - Barakatullah, Abdul Halim (Program magister Kenotariatan Fakultas Hukum Universitas Lambung Mangkurat, 2016)
Abstract: Standard contract in electronic transactions in the business-to-consumer as contract online is offered by business actor to consumers in the form of ‘take it or leave it’. Almost all standard contracts in electronic transaction cannot be negotiated. These contracts are businesses utilized to circumvent and ignore the rights of electronic consumers. This electronic transaction has its own characteristics when compared to conventional transactions. Based on the principle of contract freedom, then the contract can be made in any form and binding as law for the parties. Therefore the consumer protection should be equated with consumer conducting transactions conventionally. Under the provisions of UUPK stated that businesses are prohibited from creating a standard clause in the contract that the form of the transfer of responsibility. Consequently, the violation of the provisions of the standard clause that has been set by the business is declared null and void. The principle of responsibility is also adopted in principle of the presumption of UUPK is to always be responsible (presumption of liability principle) by the burden of reversed proof. For greater protection for consumers in electronic transactions, it is right in Indonesia to implement the principle of absolute liability in providing maximum legal protection for consumers in transactions in cyberspace.